1998
DOI: 10.1557/proc-517-383
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Thin DLC Films Using Film Stress and Raman Techniques

Abstract: Diamond like carbon (DLC) films are deposited on thin film heads in the magnetic recording industry to reduce friction and “stiction” and to provide a durable, abrasion resistant coating. The films are a mixture of graphitic phases with sp2 bonding and diamond phases with sp3 bonding. The present work provides the results of thin film stress measurements and Raman tests performed on 10 rim DLC films deposited on 75 mm silicon test wafers using standard optical lever techniques. Stress is measured after deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…The position of the G peak is seen to increase with temperature; an effect which we associate with the films becoming more graphite-like. Turlo et al [11] have also reported a trend similar to our observation in the Raman spectra of their thermally annealed DLC films. They found a shift in the G peak position of their DLC films from 1514 to 1577 cm −1 during annealing to 500 • C and the I (D)/I (G) ratios rose from 0.205 to 0.818.…”
Section: Resultssupporting
confidence: 90%
“…The position of the G peak is seen to increase with temperature; an effect which we associate with the films becoming more graphite-like. Turlo et al [11] have also reported a trend similar to our observation in the Raman spectra of their thermally annealed DLC films. They found a shift in the G peak position of their DLC films from 1514 to 1577 cm −1 during annealing to 500 • C and the I (D)/I (G) ratios rose from 0.205 to 0.818.…”
Section: Resultssupporting
confidence: 90%